P-B4 Predictors of sustained viral response to 4–6 week duration therapy with Ledipasvir + Sofosbuvir + Gs-9451 +/− Gs-9669 in early and advanced fibrosis (Nih-Ihv synergy trial). (January 2016) - Kattakuzhy, Sarah; Wilson, Eleanor; Tang, Lydia; Price, Angie; Nelson, Amy; Silk, Rachel; Gross, Chloe; Akoth, Elizabeth; Kohli, Anita; Osinusi, Anu; Masur, Henry; Kottilil, Shyamasundaran
Abstract : Background: Directly-acting antivirals (DAA) have streamlined the treatment of hepatitis C, however, limited data exists to define minimum duration of therapy. The aim of this study is to further elucidate treatment length and predictive factors of response in early and advanced fibrosis patients treated with combination DAA therapy. METHODS: In this single- center, open label, phase 2a trial, 100 HCV monoinfected participants were sequentially enrolled into three treatment arms. Treatment naive (TN) patients with F0–F2 fibrosis received LDV/SOF+GS-9451 (n = 25) or LDV/SOF+GS-9451+GS-9669 (n = 25) for 4 weeks. Patients with F3–F4 fibrosis received LDV/SOF+GS-9451 for 6 weeks [n = 25 TN & n = 25 IFN-Treatment Experienced (TE)]. HCV RNA was measured using Roche COBAS Taqman v2.0 assay with a LLOQ of 25 IU/mL. Primary endpoint was sustained virologic response defined as HCV RNA BLLOQ 12 weeks post-treatment (SVR12). Pretreatment serum samples were analyzed for resistance-associated variants (RAV) using the Illumina deep sequencing platform. Results: In the early fibrosis cohort, 10/25 (40%) patients receiving LDV/SOF+GS-9451 achieved SVR12, and 5/25 (20%) receiving LDV/SOF+GS-9451+GS-9669 achieved SVR12, with one patient lost to follow up. Baseline HCV VL >6 million was a predictor of relapse in univariate analysis and no patient with RAVs conferring >20 fold resistance achieved SVR. In the advanced fibrosis cohort, 37/50 (74%) achieved SVR, with no correlates of response on univariate analysis. TN (68%) and TE (80%) patients had no significant difference in response rate. In the TN cohort, 2 patients were lost to follow up. Conclusions: In this cohort study, combination DAA treatment resulted in moderate rates of SVR when given for six weeks, but was not effective for four weeks. Patients with high baseline VL and resistance mutants are likely to relapse with 4 week therapy. Larger studies are required to further characterize the biologic correlates in the unique group of responders to short duration therapy.